2009
DOI: 10.1016/j.socscimed.2009.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Why do people cooperate with medical research? Findings from three studies

Abstract: In this paper, we distinguish decisions about cooperation from decisions about research participation. We offer an empirical and theoretical exploration of why people in three different UK-based medical research projects chose to cooperate. Data analysis of the accounts of 128 participants across the three studies was based on the constant comparative method.Participants' cooperation was engaged by a perception that they would be contributing to the 'public good', but they also wanted to justify their decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
81
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 37 publications
6
81
0
Order By: Relevance
“…Thus, although most of our interviewees claimed they would, or indeed should, participate in research to help future patients including their family, in the main they said that they were only prepared to engage in these activities if this did not put their health needlessly at risk,17 22 23 if they might also benefit or if they had exhausted all therapeutic options. These findings recapitulate those of an earlier study that found respondents favour recruitment (without their consent) to hypothetical research studies that involve experimental drugs that their doctor thinks “might help them” rather than to placebo-based randomised controlled trials and also rate the less invasive interventions as more acceptable 24.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, although most of our interviewees claimed they would, or indeed should, participate in research to help future patients including their family, in the main they said that they were only prepared to engage in these activities if this did not put their health needlessly at risk,17 22 23 if they might also benefit or if they had exhausted all therapeutic options. These findings recapitulate those of an earlier study that found respondents favour recruitment (without their consent) to hypothetical research studies that involve experimental drugs that their doctor thinks “might help them” rather than to placebo-based randomised controlled trials and also rate the less invasive interventions as more acceptable 24.…”
Section: Discussionmentioning
confidence: 97%
“…These findings recapitulate those of an earlier study that found respondents favour recruitment (without their consent) to hypothetical research studies that involve experimental drugs that their doctor thinks “might help them” rather than to placebo-based randomised controlled trials and also rate the less invasive interventions as more acceptable 24. Dixon-Woods and colleagues similarly observed that while the parents in their study voiced communitarian motives for research participation, they were willing to donate their child’s tissue for research only if they perceived there was no risk to their child 2 23. Our data similarly imply that there are limits to research participants’ altruism—things they will not do or risks they will not take to help others—suggesting, as Haimes and Whong-Barr contend, that the truly altruistic participant who will run any number of risks and expend a large amount of effort purely for others’ benefit is, indeed, very rare 15…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Similarly, British participants in another study expressed the benefit of having contributed to the public good, regardless of any benefit to them. 11 Conversely, in other studies, participants indicated that whatever their level of knowledge was, they would struggle to make sense of their participation in trials that randomize their allocation to vaccine or placebo. 12 Clear and accurate patient information is important in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…29 However, these findings about the practicalities of the OGTT are likely to be directly translatable to the use of this test in routine practice.…”
Section: Strengths and Limitationsmentioning
confidence: 99%